Insights into the knowledge, attitude and practices of head and neck cancer survivors at otorhinolaryngology outpatient clinic of UKM Medical Center - Mohd Razif, Shahril; Suhaina, S; Nadzirah, HZ; Razif, MMY; Kong, MH; Mawaddah, A; Nor Shahrina, MZ; Yap, WJ; Salleh, A (2015)
Cancer treatment will cause problem specifically difficulties in swallowing and xerostomia. Therefore, the objective of this study was to examine knowledge, attitude and practices of Head and Neck cancer (HNC) patients after completed treatment. A cross-sectional study was conducted among 42 HNC survivors comprising of 64.3% male and 35.7% female who comes for follow–up treatment at otorhinolaryngology outpatient clinic of UKMMC. Data on socio-demography, anthropometry and disease related information was collected. Knowledge, attitude and practices (KAP) were assessed using validated questionnaire which comprised of 20 items for knowledge with 7 domains, 6 items for attitude and 5 items for practices. Majority of subjects were Chinese (71.4%), Malay (23.8%) and Indian (4.8%) with mean aged of 58.1 ± 12.4 years. About 16.7% were underweight while 69% were in a normal BMI. Majority of survivors had Nasopharynx cancer (NPC) (47.6%), were at stage IV of cancer (41.0%) and mean duration of completed treatment were 3.2 ± 3.6 years. Overall mean score for knowledge were in the lower normal range (53.7 ±17.2%) due to low score from domain on symptoms (28.6%), managing side-effects (37.7%) and causes of cancer (38.9%). In aspect of attitude, majority of the subjects (85.7%) agreed that cancer treatment was painful and burdening their family (66.7%). The survivors believed that cancer can be prevented (50%) and recur after completion of treatment (40.5%). Based on practices, cancer survivors of stage I and II consumed more than 2 liters of water a day [OR 0.112, CI 0.01-0.71] while survivors of stage III and IV go for dental check-up every 6 month [OR 8.05, CI 1.68-38.44]. In conclusion, there is a gap in knowledge, attitude and practices among HNC survivors in managing treatment side effects. Hence, continuous education after treatment and during follow-ups should be emphasized to enhance the survivors’ knowledge and practices which may contribute to better quality of life.